Autosomal recessive late onset multisystem disorder with cerebellar cortical atrophy at necropsy: report of a family. - Harding, A E (1984)
A sister and brother developed a progressive syndrome comprising bulbar palsy, supranuclear ophthalmoplegia, facial impassivity, and cerebellar ataxia together with a mixed pyramidal and extrapyramidal deficit in the limbs, in the fourth decade of life. Their parents were unaffected and inheritance was probably autosomal recessive. The female patient, who presented initially with bulbar and extrapyramidal dysfunction, was found to have cerebellar cortical atrophy at necropsy. The basal ganglia and brainstem were normal.